Konsep Pendidikan Humanistik Dalam Al-Qur’an Surat Al-Hujurat Ayat 13 Kajian Ilmu Pendidikan Islam - izzan, ahmad; Hasanudin, Sarif Nur (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Today the education system implemented by Indonesia in schools is an adoption of the western education system, so that in developing the character of students it is still far from forming human character in the values ​​contained in the Qur'an and Sunnah, especially in the application of the concept of humanistic education. . This study aims to identify and describe the concept of Humanistic Education in the Qur'an Surah Al-Hujurat Verse 13 of the Study of Islamic Education. This research is based on a framework of thought or theory which states that Humanistic Education is education that teaches that every human being is different from one another which aims to humanize humans. This research is a type of library research, namely by conducting research on the interpretation of the commentators of Q.S Al-Hujurat verse 13 and relevant written sources on the research topic being studied. The research method used is a qualitative research method by focusing on analyzing the content of the Qur'an Surah Al-Hujurat Verse 13 and the contents of the texts of books. Based on the results of the study, it can be concluded that the humanistic education of Q.S Al-Hujurat Verse 13 within the framework of Islamic Education is a unique, independent, and creative human education system. Seeing humans as creatures created by God with certain qualities, and building human character in humans who respect human dignity as the most perfect creature. Keywords: Education, Al-Qur'an, Tafsir and Humanistic